2014
DOI: 10.1186/2052-336x-12-19
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of iron-doped TiO2 for degradation of reactive Orange16

Abstract: In this study the optimum conditions for preparing the iron-doped TiO2 nanoparticles were investigated. Samples were synthesized by sol–gel impregnation method. Three effective parameters were optimized using Taguchi method, consisted of: (i) atomic ratios of Fe to Ti; (ii) sintering temperature; (iii) sintering time. The characterization of samples was determined using X-ray diffraction, BET- specific surface area, UV- Vis reflectance spectra (DRS) and scanning electron microscope (SEM). The XRD patterns of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…The development of economy and industrialization, caused water contamination especially those contained organic dye due and phenolic compounds to its toxic and harmful, has made people take it into a serious consideration [1][2][3][4][5]. 4-Chlorophenol (4-CP) is toxic and non-biodegradable, and is present in wastewater as by-products of pulp and paper, petrochemical industries, dyestuff, and pharmaceutical [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The development of economy and industrialization, caused water contamination especially those contained organic dye due and phenolic compounds to its toxic and harmful, has made people take it into a serious consideration [1][2][3][4][5]. 4-Chlorophenol (4-CP) is toxic and non-biodegradable, and is present in wastewater as by-products of pulp and paper, petrochemical industries, dyestuff, and pharmaceutical [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, the unique properties of titanium dioxide (TiO 2 ), such as its high photocatalytic activity, high chemical stability, and low toxicity, have made it a suitable photocatalyst (19). …”
Section: Reaction Timementioning
confidence: 99%
“…Safari and his coworkers showed that the photocatalytic activity of irondoped TiO 2 was greater than TiO2, because of the smaller crystal size, and higher light absorption ability (19). Moreover, Mirovic et al showed that during 2 hours of irradiation of atrazine solution (1 mg/L) with 5 g TiO 2 (0.05%) alginate (1.5%) micro-beads, it was observed that by the end of the experiment, atrazine was being degraded up to 98%, and that the highest level of degradation was attained after 45 minutes (21).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations